Socialization of Outpatient Medical Record Filling System in Parak Karakah Community Health Center Padang - Nasution, Nurhasanah; Mayasari, Nila (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
One of the implementations of medical records that must be considered at the health center is storage. The filing/storage system is the activity of storing, organizing, or storing medical record documents to facilitate retrieval. The medical record storage system is divided into two, namely centralized (centralized) and decentralized (separate for each service). Management of medical record file storage is very important to be carried out in a health care institution because it can facilitate and speed up the retrieval of medical record files stored in storage shelves. The Storage that was not optimal and did not have a tracer form at the Parak Karakah Health Center was the reason for the service team conducting outreach regarding medical record storage. This programme was carried out on Tuesday, May 9, 2023. The socialization activity went well and smoothly. Participants were enthusiastic in understanding the material provided. Solutions to problems related to the existing storage system at Puskesmas have been submitted and take into consideration for a better future.